Implementation of Community Moral Religiosity Values in Hadith and Educational Psychology in Congregation of Al-Amin Godegan Mosque, Yogyakarta - Rohmansyah; Azam Syukur Rahmatullah; Budi Jaya Putra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Changes in society from traditional patterns to modern patterns have a significant influence on changes in behavior and lifestyle. Lifestyle changes that eliminate Islamic behavior, for example lack of respect for others and other behaviors. This activity was carried out in the godegan community. Their lives are heavily influenced by Javanese traditions. Some of them pay less attention to Islamic teachings, especially moral teachings. Even though the Prophet emphasized morals to educate children and adolescents. This service uses the lecture and learning model method. This activity aims to make people know and understand and practice the hadiths about social morality in everyday life. The results of this activity are: First, the community understands and understands the Prophet SAW's message about morals. Second, social moral education can have a better impact on change with character education in community and family life. Third, the community can understand and implement social morality that is in line with the values of religiosity contained in the hadith of the Prophet and the psychology of Islamic education.